Predictive Value of Serum p53 Antibodies in Oral Squamous Cell Carcinoma - Khan, Abbas Saleem (International Journal of Pathology, 2021)
Background: Oral cancer represents a remarkable component of global cancer burden with marked mortality and morbidity. This study is designed to determine the predictive value of serum p53 antibodies in cases of oral squamous cell carcinoma (OSCC) and among healthy individuals. Materials and Methods: A comparative cross-sectional study was conducted between April, 2016 to March, 2017; on serum samples of 120 subjects comprising of 60 OSCC cases and 60 healthy individuals, collected from oral and maxillofacial surgical units of various institutes. Serum anti-p53 Ab concentrations were determined by enzyme-linked immunosorbant assay (ELISA) at the department of Pathology (Microbiology section), Peshawar Medical College (PMC). Data was recorded, evaluated and analysed by SPSS version 20. Sensitivity, specificity, positive and negative predictive value, likelihood ratios, accuracy, misclassification rate, diagnostic odds ratio were calculated. Receiver operating characteristic (ROC) curve was plotted and area under the curve (AUC) was calculated for measuring the diagnostic accuracy. Results: Among the study participants, statistically significant difference was observed for serum p53 Ab levels and status. The ROC curve analysis (AUC=0.852) suggested that the p53 seropositivity can significantly discriminate between the cases of OSCC and healthy individuals. Conclusion: The present study showed that serum p53 antibodies could be a useful test due to its high sensitivity for p53 seropositivity among subjects of OSCC and healthy individuals.